Downscaling of seasonal ensemble forecasts to the convection‐permitting scale over the Horn of Africa using the WRF model. (10th October 2020) - Mori, Paolo; Schwitalla, Thomas; Ware, Markos Budusa; Warrach‐Sagi, Kirsten; Wulfmeyer, Volker
Abstract: The new SEAS5 global ensemble forecast system was dynamically downscaled over the Horn of Africa for summer (June‐July‐August) 2018. For this purpose, a multi‐physics ensemble was designed with a grid increment of 3 km and without any intermediate nest based on the Weather Research and Forecasting model (WRF). The WRF and the SEAS5 model output were compared with each other and reference datasets to assess the biases in 4 different regions of Ethiopia. Also, the WRF ensemble variability was investigated in relation to model parameterization and lateral boundary conditions. Over the summer, the SEAS5 has a positive temperature bias of 0.17°C compared to ECMWF analysis average for the study domain, while the WRF bias is +1.14°C. Concerning precipitation, the WRF model had average accumulated values of 264 mm, compared to 248 mm for SEAS5 and 236 mm for the observations. Over south Ethiopia, however, the downscaling produced over 50% more precipitation than the other datasets. The maximum northward extension of the tropical rain belt was reduced by about 2° in both models when compared to observations. Downscaling increased reliability for precipitation, correcting the SEAS5 underdispersion: ensemble spread for precipitation was increased by about 70% in the WRF ensemble in three of the four Ethiopian sub‐regions, whereas the very dry Somali region remained unaffected. The WRF ensemble analysis revealed that the ensemble spread is mainly caused by the perturbed boundary conditions, as their effect is often 50% larger than the physics‐induced variability in the mountainous part of Ethiopia for precipitation and temperature. Abstract : The SEAS5 seasonal ensemble forecast was dynamically downscaled for summer 2018 over Ethiopia using a multi‐physics ensemble based on the WRF model. The WRF limited‐area model at the convection‐permitting resolution shows a wet and warm bias with respect to the reference datasets, but ensemble spread and reliability for precipitation are improved compared to the forcing model. Perturbed lateral boundary conditions were responsible for larger ensemble spread of temperature and precipitation over the Ethiopian highlands compared to physics perturbations.